Translation Techniques Used in Translating Non- Standard English Words in The Fast and Furious Movie - Kresnu Ahda Yudyantama; Arso Setyaji; Rahmawati Sukmaningrum (Universitas PGRI Semarang, 2023)
This study examines the translation approaches utilized to translate non-standard English in The Fast and the Furious: Tokyo Drift's screenplay. This study employed qualitative methods. In this study, the researcher assessed the translation technique of 102 non-standard English words from the script for The Fast and the Furious: Tokyo Drift. Molina and Albir's notion of translation procedures was utilized by the researchers. In this study, the researcher found 9 kinds of translation techniques such as literal, established equivalent, adaptation, borrowing, linguistic compression, generalization, reduction, linguistic amplification, particularization. Moreover, the dominant translation technique is literal translation technique used 35 times with percentage 54,61%% from the data, followed by established equivalent 18,44% used 13 times, adaptation with 7,15% used 5 times, borrowing with 7,15% percentage from the data used 5 times, linguistic compression with percentage 3,57% used 3 times, generalization used 2 times with percentage 2,75%, reduction used 2 times with percentage 2,75%, linguistic amplification used 1 time with percentage 1,79%, and particularization percentage 1,79% used 1 time. Since the script for the Fast and the Furious movie contains many words and phrases that are not considered standard English, it makes sense that the translators would prefer the literal translation process, which includes providing an exact word-for-word counterpart. Because it uses an equivalence-based approach rather than a literal one, this method is more flexible than literal translation